Answer:
the magnitude of the error is 2.9959 × 10⁻⁹
Step-by-step explanation:
By Alternating series estimation theorem
[tex]\sum ^{\infty}_{n=1}(-1)^{n+1}a_n=a_1-a_2+a_3-a_4...+a_n[/tex] is satisfies
(i) [tex]a_n +1\leq a_n[/tex] for all n
(ii) [tex]\lim_{\rightarrow \infty}a_n=0[/tex]
The formula for magnitude of error is
[tex]|R_n|=|s-s_n|\leq a_n+1[/tex]
Let [tex]a_n = \frac{(0.08)^n}{n}[/tex]
We can see [tex]\frac{(0.08)^n^+^1}{n} \leq \frac{(0,08)^n}{n}[/tex]
For all n ∈ N
That means [tex]b_{n+1}\leq b_n[/tex] for all n ∈ N
[tex]\lim_{n \rightarrow \infty}a_n=\lim(\frac{(0.08)^n}{n} )\\\\=\frac{(0.08)^{\infty}}{\infty}[/tex]
[tex]\lim_{n\rightarrow \infty}a_n =0[/tex]
The alternating series estimation theorem is [tex]|R_s| = |s-s_n|\leq a_{n+1}[/tex]
After stop adding the term with n = 6
the series tells that the error is smaller than the term with a
Therefore
[tex]a_7 = \frac{(0.08)^7}{7} \\\\= \frac{20.97152}{7} \times 10^-^9\\\\=2.9959\times10^-^9[/tex]
the magnitude of the error is 2.9959 × 10⁻⁹